The relationship between grit, resilience and physical activity: a systematic review - Martin, Joel; Hromyak, Ashley; Sax van der Weyden, Megan; Weinstein, Ali A.; Boolani, Ali (Frontiers in Sports and Active Living, 2025)
IntroductionAt present only about half of Americans meet the recommended physical activity (PA) guidelines. Theoretically personality traits, encompassed by grit and resilience, should be beneficial to overcome common barriers to PA participation. To systematically review synthesized literature regarding the relationship between grit, resilience, and PA outcomes.MethodsThe search methodology adhered to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. Study eligibility criteria included peer-reviewed studies with healthy adult participants, where a reported relationship between PA and either grit or resilience existed. Study quality was evaluated with the Appraisal Tool for Cross-Sectional Studies (AXIS) and a qualitative synthesis was performed.ResultsA total of 33 studies involving diverse participants (n = 37,370) across age, sex, culture, education, and PA outcomes met the inclusion criteria. The methodological quality of studies was rated as good on average. Most of the studies found positive relationships between grit, resilience, and PA outcomes, such as adherence, intensity, and performance in competitive settings.ConclusionCumulatively, the findings suggest that personality traits of grit and resilience play a significant role in supporting PA engagement, with individuals exhibiting higher levels being more likely to participate in regular PA and achieve better performance outcomes. Given that most studies employed cross-sectional designs, future research is needed to elucidate whether a causal relationship exists between grit, resilience, and PA. These findings may have practical applications for designing interventions aimed at fostering these traits to enhance PA adherence and overall health.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022370061, identifier CRD42022370061.